Diagnostic Coding of Elder Mistreatment: Results From a National Database of Medicare Advantage and Private Insurance Patients, 2011–2017. (April 2022) - Rosen, Tony; Wen, Katherine; Makaroun, Lena K.; Elman, Alyssa; Zhang, Yiye; Jeng, Philip J.; LoFaso, Veronica M.; Lachs, Mark S.; Clark, Sunday; Bao, Yuhua
Health care providers may play an important role in detection of elder mistreatment, which is common but underrecognized. We used the Health Care Cost Institute insurance claims database to describe elder mistreatment diagnosis among Medicare Advantage (MA) and private insurance patients in the United States from 2011 to 2017. We used International Classification of Diseases (ICD) coding to identify cases, examining the impact of transition from ICD-9 (Ninth Revision) to ICD-10 (Tenth Revision), which occurred in October 2015 and added 14 new codes for "suspected" mistreatment. 8, 127 patients (0.051% of all aged ≥ 65), including 6, 304 with MA (0.058%) and 1, 823 with private insurance (0.026%) received elder mistreatment diagnosis. Transition from ICD-9 to ICD-10 was associated with a small increase in diagnosis rate, with "suspected" codes used in 45.3% of ICD-10 versus 9.7% of ICD-9 cases. Overall rates remained low. Rates, settings, and types of diagnosis differed between MA and private insurance patients.